Analysis of The Impact of Information Quality and Social Media Services on The Loyalty Commitment of Generation Z E-Commerce Users in Medan - Austin Alexander Parhusip; Pasaman Silaban; Robert Tua Siregar (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of information quality and social networking services on the commitment loyalty of Generation Z users of e-commerce platforms in Medan. Using a quantitative approach with a sample of 100 Generation Z respondents who shop online, data was collected through a Likert scale-based questionnaire and analyzed using multiple linear regression. The results of the study indicate that: (1) information quality has a positive and significant effect on commitment loyalty (t=3.969, sig=0.000); (2) social networking services have a positive and significant effect on commitment loyalty (t=3.601, sig=0.001); and (3) both variables together have a significant influence on loyalty commitment (F=49.101, sig=0.000). The coefficient of determination (R²) of 0.493 indicates that 49.3% of the variation in loyalty commitment can be explained by information quality and social media services. This study underscores the importance of accurate, comprehensive information and authentic social interaction in enhancing e-commerce user loyalty. The practical implication is that e-commerce platforms need to optimize information quality and leverage social media to build emotional connections with Generation Z consumers